The science book - Hart-Davis, Adam; Lamb, Hilary; Farndon, John; Green, Dan, 1975 June 20-; Harvey, Derek; Johnson, Penny, 1960-; Palmer, Douglas; Parker, Steve, 1952-; Sparrow, Giles, 1970- (Big ideas simply explained., 2025)
An innovative and accessible guide to theories in technology and nature. Learning about science can be daunting, but this book makes it easier by giving you all the big ideas simply explained. Simple explanations and stylish infographics open up the world of science to even the complete novice.